Causal Association Between Monounsaturated Fatty Acids and Lung Cancer: A Two‐Sample Mendelian Randomization Study - Shaofeng Zhang; Jia Jiang; Xiping Wu; Jiayi Liu; Wei Lei; Siqin Chen; Yaling Zeng; Xiang Liu; Qiang Xiao (The Clinical Respiratory Journal)
ABSTRACT Objective This study aims to investigate the potential causal relationship between monounsaturated fatty acids (MUFAs) and lung cancer. Methods Genetic data on MUFAs and pathological subtypes of lung cancer were extracted from genome‐wide association studies (GWAS). The primary analysis utilized inverse‐variance weighted analysis (IVW), with additional methods including the weighted median method, MR‐Egger regression method, and weighted model method. Sensitivity analysis was conducted to assess the robustness of the findings. Results The inverse variance–weighted (IVW) analysis of monounsaturated fatty acids in relation to lung adenocarcinoma yielded an odds ratio (OR) of 1.059 with a 95% confidence interval of 0.960 to 1.168 and a p value of 0.252. Similarly, for lung squamous cell carcinoma, the IVW analysis produced odd ratios of 0.884, 95% confidence intervals of 0.747 to 1.045, and a p value of 0.148. In the case of small cell lung cancer, the odds ratio was 0.936, the 95% confidence interval was 0.751 to 1.166, and the p value was 0.554. Conclusion It can be concluded that there is no direct causal relationship between monounsaturated fatty acids and the development of lung cancer.